PTU-088 De Novo Cirrhosis in Old Age is Associated with Significant Delays in Diagnosis, High Incidence of Decompensation at Presentation and High Mortality. (17th August 2016) - Ghuman, S; Czajkowski, M; Hewitt, J; Yeoman, A; Gardezi, A
Abstract : Introduction: Mortality related to end-stage liver disease is increasing. Coupled with an ageing population, this will lead to increasing numbers of those aged over 65 with a de novo diagnosis of cirrhosis. However, the incidence and clinical behaviour of cirrhosis in old age is not well understood. Our aim was to evaluate and elucidate the characteristics of cirrhosis in elderly patients. Methods: All patients aged over 65 with a diagnosis of cirrhosis at our institution were identified using the health board electronic record. Data on patient demographics, date and method of diagnosis, liver function tests (LFTs), MELD scores, presence of decompensation and outcomes (varices, renal impairment, hepatocellular carcinoma [HCC], death) were collected and analysed. Results: 395 cirrhotics aged over 65 were identified. Clinical details were unavailable for 12, 7 had received a liver transplant and 81 were first diagnosed under 65 hence excluded from analysis. Median age was 74 (65–92) and 179/295 (60.7%) were male. The commonest aetiologies of cirrhosis were alcohol (86/295), cryptogenic (81/295) and NASH (62/295). Mode of diagnosis was a combination of laboratory and imaging features (USS, CT or MRI) in 86.8%, liver biopsy in 8.8% and fibroscan in 4.4%. Abnormal LFTs prior to diagnosis were found in 90.5%. Importantly, median delay in diagnosis of cirrhosis from first abnormal LFT was 72 months (1–168). Consequently, 54.6% were decompensated at first presentation. For the cohort, median MELD score was 9 (6–40) at diagnosis. In terms of complications, 139/295 (47.1%) developed ascites, 41/295 (13.9%) had atleast one episode of hepatic encephalopathy and 93/295 (31.5%) developed varices of whom, 24.7% bled. Renal impairment was common, occurring in 164/295 (55.6%). This comprised one or more episodes of acute kidney injury (AKI) in 113/164 (68.9%) and pre-existing CKD in the remainder. Importantly, HCC was diagnosed in 61/295 (20.7%); identified at diagnosis of cirrhosis in 72.1%. Active treatment for HCC occurred in 57.5%; the remainder palliated. Over half the cohort (58.8%) had died at the time of analysis, with median time from diagnosis of cirrhosis to death 13 months (0–116). In the compensated cirrhotics the median was 26 months versus only 9 months in those decompensated at presentation (p = 0.0027). Conclusion: De novo cirrhosis in the elderly is associated with significant delays in diagnosis from time of first abnormal LFT, high incidence of decompensation, renal impairment and HCC. Consequently short term mortality is high. Abnormal LFTs should therefore not be ignored. Furthermore, in those with established cirrhosis, close attention should be paid to renal function and potential impact of concomitant diseases and polypharmacy on this. Disclosure of Interest: None Declared